Assessment of Strength Properties of Concrete Produced Using Scoria as Coarse Aggregates. - Kasozi, Chrisestom (Kabale University, 2023)
This study aimed to assess the strength properties of concrete produced using scoria as coarse aggregates. Scoria is a volcanic rock that is abundantly available in some regions and has the potential to be used as a sustainable alternative to traditional coarse aggregates. In this research, three concrete mixtures, C25, C30 and C35 were designed with 100% of scoria as coarse aggregates and natural fine aggregates. Properties considered included: workability, unit weight and compressive strength. Test results indicated that developing scoria-based concretes using locally available Scoria lightweight aggregates seems to be feasible. The findings showed that in all cases, scoria concrete gave lesser compressive strength than would be expected from the conventional concrete. The compressive strength curves plotted for the scoria concrete mixes developed in this investigation were comparable to typical compressive strength curves for normal weight concrete with relatively better capacity at failure than scoria concrete. In conclusion, this study suggests that scoria can be used as a viable alternative to traditional coarse aggregates in the production of concrete with acceptable strength properties for structural applications in floor slabs. Further research should however be carried out to investigate the long-term durability and performance of scoria-based concrete and to study its microstructure.